2004
DOI: 10.1038/sj.onc.1208112
|View full text |Cite
|
Sign up to set email alerts
|

β-parvin inhibits integrin-linked kinase signaling and is downregulated in breast cancer

Abstract: We analysed breast tumors and breast cancer cell lines for the expression of b-parvin (ParvB), an adaptor protein that binds to the integrin-linked kinase (ILK). Quantitative RT-PCR indicated that ParvB mRNA was downregulated, by at least 60%, in four of nine breast tumors, relative to patient-matched normal mammary gland tissue. We also found that ParvB protein levels were reduced by X90% in five of seven advanced tumors, relative to matched normal breast tissue. Conversely, ILK protein and kinase activity le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(75 citation statements)
references
References 55 publications
(61 reference statements)
3
70
1
1
Order By: Relevance
“…PARVB (which encodes PARVIN ) mRNA and protein levels are markedly downregulated in a number of advanced breast tumours 36 and its expression is inversely correlated with ILK protein and kinase activity levels, suggesting that down-regulation of PARVB expression upregulates ILK activity in human tumours (Table 1). Regarding PINCH1/2 expression in samples of breast, prostate, lung, colon, and skin carcinomas, both proteins have been found to be upregulated in tumour-associated stromal cells, especially at the tumour invasive edges 37 .…”
Section: Integrin Adaptors In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…PARVB (which encodes PARVIN ) mRNA and protein levels are markedly downregulated in a number of advanced breast tumours 36 and its expression is inversely correlated with ILK protein and kinase activity levels, suggesting that down-regulation of PARVB expression upregulates ILK activity in human tumours (Table 1). Regarding PINCH1/2 expression in samples of breast, prostate, lung, colon, and skin carcinomas, both proteins have been found to be upregulated in tumour-associated stromal cells, especially at the tumour invasive edges 37 .…”
Section: Integrin Adaptors In Cancermentioning
confidence: 99%
“…Recently, a new function of ILK in the regulation of the microtubule cytoskeleton and mitotic spindle organization has been proposed 103 High levels of PARVIN correlate with increased cell adhesion, induce reversal of anchorageindependent growth 36 , and attenuation of tumour growth in nude mice 110 . The latter tumoursuppressive role of PARVIN is consistent with deletions observed in its locus (22q13.21) in some colon and breast cancer cells 111 .…”
Section: The Ipp Complex (Ilk/pinch and Parvin) And Cancer Biologymentioning
confidence: 99%
“…It has also been shown that actopaxin (␣-parvin) and affixin (␤-parvin) compete for ILK binding (42). These interactions exert opposing effects on ILK kinase activity (25,43). Due to the negative regulation of TESK1 activity by actopaxin reported herein, it will be important to determine whether ␤-parvin binds TESK1 and if so how this may affect its activity.…”
Section: Fig 11mentioning
confidence: 99%
“…ILK modulates integrinmediated adhesion by directly interacting with the cytoplasmic tails of b1-or b3-integrin receptors (Hannigan et al, 1996), and complexes with Parvin A/B (Attwell et al, 2003;Mongroo et al, 2004) and PINCH (Tu et al, 1999). More recently, ILK has also been shown to have an instrumental role in the proper organization of the mitotic spindle during cell division (Fielding et al, 2008).…”
Section: Introductionmentioning
confidence: 99%